BURNOUT DAN KINERJA PERAWAT PELAKSANA DI RUMAH SAKIT - Najoan, Zefanya; Pondaag, Ferlan; Natalia, Adriani (Lasalle Health Journal, 2023)
Introduction: Physical, mental or emotional fatigue experienced by a nurse is a phenomenon that can describe burnout. When nurses start to feel boredom at work, the work environment will become unconducive. If this situation is allowed to drag on, it will cause nurse productivity or performance to decline. The negative impact will be felt by patients and families, colleagues, and management where nurses work. Objective: The study aims to find out burnout’s relationship with the performance of executive nurses at one of the hospitals in Sonder, Minahasa. Method: The study is a quantitave study with correlation analysis, to see if there is a link between variables with the cross-sectional study approach. The sample in this study is the managing nurse of 53 people who were procured using a total sampling. Research instruments using an MBI questionnaire (Maslach Burnout Inventory) and the 2017 formal performance questionnaire was then analysed using a spearmen test. Results: Based on the research results obtained, the value of p = 0.002 (α<0.05) so this shows that there is a relationship between burnout and the performance of implementing nurses, where the correlation coefficient number 0,412, which means that a variable relationship is strong enough with a a positive value and the therefore makes the two variables one way or another. Conclusion: From this research the heavier the burnout, the less the performance of the executive nurse will be.